PRODUÇÃO DE BIODIESEL E SABÃO A PARTIR DE ÓLEOS RESIDUAIS NA REGIÃO DE MACHADO - MG. - Leite, Vera Lúcia Araújo (2010)
The present study aimed at testing the possibility of using residual oil in biodiesel production, thus reducing the amount of this oil that is released daily in the sewer system and causes much of water pollution. Five treatments were carried through in laboratory procedures. They consisted of biodiesel production with refined soybean oil by methyl and ethylic route; biodiesel production from waste oil by ethylic route with water addition at the end of the transesterification process; biodiesel production from washed residual oil, by alcoholic route, with or without water addition at the end of the transesterification process. The biodiesel production was also tested at the plant with refined soybean oil and residual oil. Laboratory results have shown that the biodiesel production using non-residual oil, by methyl route, has the same yield of the ethylic route. The use of washed residual oil with water addition at the end of the process allows the production of biodiesel with visual quality similar to that of non-residual oil obtained through laboratory procedures and with return 5% lower than non-residual oil. The yield of biodiesel at the plant was around 80% for residual or non-residual, indicating that biodiesel yield may be lower in large-scale production than in laboratory production processes, getting an average production of 300 liters of biodiesel for each 300 liters of vegetable oil.